An increased percentage of myeloid CD34+ bone marrow cells stratifies intermediate IPSS‐R myelodysplastic syndrome patients into prognostically significant groups. (18th May 2018) - Chen‐Liang, T.‐H.; Casado‐Prieto, A. M.; Campos‐Rodríguez, V.; Hurtado, A. M.; Amigo, M. L.; García‐Malo, M. D.; Vicente, V.; Ortuño, F. J.; Jerez, A.
Abstract: Introduction: The Revised International Prognostic Scoring System (IPSS‐R) for myelodysplastic syndromes (MDS) has established an intermediate category where a disease‐modifying intervention is a matter of debate. Flow cytometry allows us to determine a fraction of immature myeloid cells in a semiautomated procedure. The aim of this study, mirroring IPSS‐R study inclusion criteria, was to test whether bone marrow (BM) CD34+My percentage has independent prognostic value in the MDS setting. Methods: BM CD34+My cells were quantified, at diagnosis, selecting CD34+/CD45+/CD11b±/CD13+. Patients were excluded when receiving treatment for altering the natural course of the disease and when IPSS‐R could not be calculated due to the lack of metaphases. Finally, Cox analyses were performed, on a series of 260 patients, for overall survival (OS) and time to acute myeloid leukemia (AML) transformation. Results: By analyzing ROC curves, the most accurate prognostic variable, regarding blasts by cytology and CD34+ by cytometry, was the percentage of blasts by microscopy. The percentage of CD34+My in BM showed an AUC of 0.767 and 0.576 for time to AML transformation and OS, respectively. When performing a multivariate regression including the IPSS‐R and the percentage of BM CD34+My cells >1%, both factors predicted for a shorter time to AML transformation. In addition, CD34+My percentage successfully stratified the intermediate IPSS‐R category into two prognostic groups with a relative risk of 5.73 (95% CI [1.2‐27.8]; P  =   .03). Conclusion: We found that BM CD34+My percentage has an independent value concerning the IPSS‐R, especially relevant for the prediction of transformation to AML and within the intermediate group.